The Implementation of the Academic Writing Course Syllabus - Bastian, Grace S. (Widya Mandala Surabaya Catholic University, 2016)
Curriculum change required to meet the stakeholders’ needs, whether it occurs in regular bases or in responding towards some dissatisfaction of students’ learning outcomes. This study was trig-gered by the second reason. To be more specific, it focused on how the syllabus was implemented in terms of teaching materials, classroom exercises, home assignments, and final projects. Document analyses were conducted and were validated using instrument triangulation. A semi structured inter-view was given to 18 first semester graduate students of 2013-2014 academic year. The findings were intended as a contribution and feedback towards the teaching-learning process of Academic Writing course at the English Education Department, Graduate School, Widya Mandala Catholic University Surabaya. From the analyses, it showed that the course syllabus was implemented in accordance with the learning objectives. However, there were some items evaluated in the students’ result which had not met the objectives as written in the syllabus. The gap was ultimately noted as the consequence that students were not accustomed to use the academic writing manual, and they were short of academic writing practice. Hence, some suggestions were proposed to give them more sustainable tasks to use the format, read and analyze more journal articles, as the model of writing. The result of this study was supposed to give contribution not only to the improvement of the institution’s curriculum, but also to wider pedagogical content knowledge, mainly on English as Foreign Language (EFL) teach-ing.